"OneScreen" Drug Test Devices: Adulterant Effects and Untrained Subject Use. - ALBRITTAIN, EMMA; BOWEN, KYLE; DAVIS, DIANE (Clinical Laboratory Science)
Objective: To evaluate the CLIA-waived immunochromatographic lateral flow assay "OneScreen" drug test device from American Screening Corporation for its ability to perform accurately in the presence of urine specimen adulterants and to evaluate the ability of untrained subjects to perform the assay with competence. Design: The device used in this study detected five drugs/drug classes and measured specific gravity and creatinine to detect adulteration. The five drug analytes were tetrahydrocannabinol metabolite (THC), 3,4-methylenedioxy-N-methylamphetamine (MDMA or Ecstasy), methamphetamine, cocaine metabolite (benzoylecgonine) and opiates. A specimen positive for all 5 drugs was created with high enough drug concentrations that dilution alone by an adulterant would not cause the specimen to test negative. This specimen was adulterated with varying concentrations of 11 adulterants: Visine® eye drops, bleach, vinegar, salt, hand soap, ammonia, ethanol, hydrogen peroxide, isopropanol, acetone and baking soda. After the study protocol was cleared by the Salisbury University (SU) Human Subjects Committee, subjects were recruited to test 3 specimens: a specimen positive for one drug, yellow colored water to mimic a diluted specimen and a urine specimen adulterated with enough bleach to give a false negative. After obtaining informed consent and providing safety instruction and protective equipment, subjects were given an expired device kit with all accompanying literature and asked to perform testing on the three specimens without any assistance. Subjects completed a report form and answered questions related to demographics and their reactions to the testing process. Setting: Salisbury University Medical Laboratory Science Program laboratories, Salisbury, MD Participants: Sixteen students from Salisbury University volunteered for this study, four students from each of Salisbury University's four schools of learning (Science and Technology, Business, Education and Professional Studies, and Liberal Arts). Each student was a senior in good academic standing. The students were from several majors and their level of selfreported laboratory expertise varied widely. Main outcome measures: For adulterant testing, the outcomes were the effects on the device testing areas for the control, positive test, creatinine and specific gravity as well as the physical alteration and odor of the specimen. For the subjects performing testing, the outcomes were demographic data, time spent reading instructions, physical performance of the test, interpretation of results, confidence in results and recommendations for further action. Results: Most adulterants either failed at causing a false negative and/or were detectable as adulterants by odor, physical appearance and/or alterations in specific gravity/creatinine. Vinegar, bleach and ethanol were the only adulterants deemed effective in creating a false negative result; however, vinegar and bleach failed creatinine/specific gravity measurements at fairly low concentrations, and ethanol caused false negatives only at a high concentration. Although the subjects could correctly identify positive, negative and invalid test results, more than a third had difficulty getting proper flow in the devices. Although 87% of subjects reported that they understood the instructions and 81.5% felt confident in their results, no subjects noticed the expired date on the devices or the bleach odor. Subjects either failed to recognize abnormal creatinine and specific gravity or noticed the abnormalities but did not interpret them as signs of adulterated specimens. Seventy-five percent of the subjects recommended additional testing, even though they expressed confidence in their results. Conclusion: The adulterants that interfered with these devices (bleach, vinegar and ethanol) could easily be detected by alterations in creatinine, specific gravity and/or odor. The data suggests that although the test devices are designed for intuitive and easy use, performance of untrained subjects is imperfect and the potential exists for dangerous misinterpretation of testing results and failure to identify adulterated specimens.